Automatic patient positioning and gating window settings in respiratory‐gated stereotactic body radiation therapy for pancreatic cancer using fluoroscopic imaging. (27th January 2018) - Pettersson, Niclas; Simpson, Daniel; Atwood, Todd; Hattangadi‐Gluth, Jona; Murphy, James; Cerviño, Laura
Abstract: Before treatment delivery of respiratory‐gated radiation therapy (RT) in patients with implanted fiducials, both the patient position and the gating window thresholds must be set. In linac‐based RT, this is currently done manually and setup accuracy will therefore be dependent on the skill of the user. In this study, we present an automatic method for finding the patient position and the gating window thresholds. Our method uses sequentially acquired anterior–posterior (AP) and lateral fluoroscopic imaging with simultaneous breathing amplitude monitoring and intends to reach 100% gating accuracy while keeping the duty cycle as high as possible. We retrospectively compared clinically used setups to the automatic setups by our method in five pancreatic cancer patients treated with hypofractionated RT. In 15 investigated fractions, the average (±standard deviation) differences between the clinical and automatic setups were −0.4 ± 0.8 mm, −1.0 ± 1.1 mm, and 1.8 ± 1.3 mm in the left–right (LR), the AP, and the superior–inferior (SI) direction, respectively. For the clinical setups, typical interfractional setup variations were 1–2 mm in the LR and AP directions, and 2–3 mm in the SI direction. Using the automatic method, the duty cycle could be improved in six fractions, in four fractions the duty cycle had to be lowered to improve gating accuracy, and in five fractions both duty cycle and gating accuracy could be improved. Our automatic method has the potential to increase accuracy and decrease user dependence of setup for patients with implanted fiducials treated with respiratory‐gated RT. After fluoroscopic image acquisition, the calculated patient shifts and gating window thresholds are calculated in 1–2 s. The method gives the user the possibility to evaluate the effect of different patient positions and gating window thresholds on gating accuracy and duty cycle. If deemed necessary, it can be used at any time during treatment delivery.